Heart rate variability, thyroid hormone concentration, and neuropsychological responses in Brazilian navy divers: a case report of diving in Antarctic freezing waters - BRUZZI,RÚBIO S. (2022)
Abstract Open-water diving in a polar environment is a psychophysiological challenge to the human organism. We evaluated the effect of short-term diving (i.e., 10 min) in Antarctic waters on autonomic cardiac control, thyroid hormone concentration, body temperatures, mood, and neuropsychological responses (working memory and sleepiness). Data collection was carried out at baseline, before, and after diving in four individuals divided into the supporting (n=2) and diving (n=2) groups. In the latter group, autonomic cardiac control (by measuring heart rate variability) was also assessed during diving. Diving decreased thyroid-stimulating hormone (effect size = 1.6) and thyroxine (effect size = 2.1) concentrations; these responses were not observed for the supporting group. Diving also reduced both the parasympathetic (effect size = 2.6) and sympathetic activities to the heart (ES > 3.0). Besides, diving reduced auricular (effect size > 3.0), skin [i.e., hand (effect size = 1.2) and face (effect size = 1.5)] temperatures compared to pre-dive and reduced sleepiness state (effect size = 1.3) compared to basal, without changing performance in the working memory test. In conclusion, short-term diving in icy waters affects the hypothalamic-pituitary-thyroid axis, modulates autonomic cardiac control, and reduces body temperature, which seems to decrease sleepiness.